Principal component analysis for concrete mix by ranking method - Mani Deepika, A; Vijaya Gowri, T; Sravana, P (International Journal of Engineering and Technology, 2018)
Cement concrete mixture design for pavement was studied through a series of laboratory experiments based on an actual project program. The main purpose of this research is to investigate the minimum cement content required with an appropriate water-cement ratio (w/c) to meet given workability, strength, and durability requirements in a concrete pavement; and to reduce costs. An experimental program was conducted to test [9] concrete mixtures, designed according to Taguchiâ€™s orthogonal selection with w/c of 0.36, 0.45 and 0.55 and cured by different methods such as Air Curing (AC), Water Curing (WC) and Plastic Bag Curing (PBC) separately. Compressive strength (CS) of 150mm cubes are found for [3-7] and14 days. Cube compressive strength, water to cement ratio (w/c), Cement, Coarse Aggregate, Fine Aggregate were the parameters to be used for optimization by varying water-cement ratios, cement quantities, Coarse Aggregate (CA) quantities and Fine Aggregates (FA) quantities. The data sets of mix designs were analyzed by Principal Component Analysis (PCA) to draw most influencing variables on the performance of concrete. From the analysis, it is found that w/c is the most influencing ingredient in case of AC and PBC and CA for WC on Compressive Strength of concrete.Â Â